I would answer that but to bissy finding my mine answer
Answer: X = 7
Step-by-step explanation:
Or, you don't have to plug any of those in and solve for x
subtract 6 from both sides
2x = 14
divide 14 by 2x
x=7
Answer:
h = yX -yr
Step-by-step explanation:
X=r-h/y
X - r = h/y
y*(X-r) = h
h = yX -yr
Answer:
43.
Step-by-step explanation:
Follow PEMDAS (Parentheses, exponents, multiply, divide, add, subtract). First you do 8-4 which is 4, then you multiply 4 by 4 which is 16 since you multiply next, then you add 27 to 16 which then gets you to 43.